Managing Crowdfunding Risks in Terrorism Financing: A Mediated Analysis of Government Intervention and Donation Intentions - Muslim, Fithriadi; Zulfa, Eva Achjani; Syauqillah, Muhamad (UI Scholars Hub, 2025)
Crowdfunding has emerged as a popular platform for collective funding of social, charitable, and commercial projects. However, its increasing use has raised concerns over potential misuse, including as a source of terrorism financing. This study investigates the relationship between donation intentions using crowdfunding and the risk of crowdfunding being used as a source of terrorism financing. Furthermore, it explores the mediating role of government intervention in this relationship. Using a Structural Equation Modeling-Partial Least Squares (SEM-PLS) second-order approach, the research evaluates the interaction between donor intentions, crowdfunding risks, and government regulations. Findings reveal that while donor intentions significantly impact the risk of crowdfunding misuse for terrorism financing, the mediating role of government intervention is statistically insignificant. This suggests that regulatory measures alone may not sufficiently mitigate these risks. These findings highlight the critical need to reevaluate current strategies for preventing the misuse of crowdfunding for illicit purposes. By providing empirical evidence of the limited impact of government intervention, this study contributes valuable insights for policymakers aiming to strengthen oversight mechanisms and ensure safer crowdfunding practices in Indonesia.